2023
DOI: 10.1108/ejim-11-2022-0610
|View full text |Cite
|
Sign up to set email alerts
|

How digital transformation helps enterprises achieve high-quality development? Empirical evidence from Chinese listed companies

Abstract: PurposeThe purpose of this study is to explore how digital transformation helps enterprises achieve high-quality development, including the mediating mechanism of information transparency, innovation capacity and financial stability, the moderating role of financing constraints and government subsidies, and the heterogeneous effects of property rights, size and growth.Design/methodology/approachThis study conducts two-way fixed-effect model using 780 samples of China's Shanghai-Shenzhen A-share listed companie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 58 publications
1
10
0
Order By: Relevance
“…Fourth, digital empowerment can improve human capital by increasing managerial efficiency and economies scale [ 87 ]. Besides production efficiency [ 84 ], our study found that managerial efficiency is also a mediating effect.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, digital empowerment can improve human capital by increasing managerial efficiency and economies scale [ 87 ]. Besides production efficiency [ 84 ], our study found that managerial efficiency is also a mediating effect.…”
Section: Discussionmentioning
confidence: 99%
“…In this paper, q ratio is used as an indicator of firms’ performance to gauge the impact of digital transformation as it enables firms to uncover new pathways of value creation, transforming value creation process [ 3 ] but such transformation entails a long range of period [ 24 ] and the investment in such strategy scarcely generates returns in the year of implementation, which cannot be measured by traditional accounting data. Therefore, the q ratio can better reflect the impact of digital transformation as it includes market information that captures a firm’s long-term performance and intangible values.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Additionally, corporate financial risks stemming from high financial leverage and challenges in securing financing, often due to substantial financing constraints, play a pivotal role in shaping the development of enterprises [ 15 ]. Embracing digital transformation can send positive signals to the market and simplify the process of accessing financing for companies [ 24 ]. This shift also contributes to the reduction of information asymmetry, as financial information becomes more transparent within the context of digital transformation [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, DT can transform a vast amount of operational data into digital resources and significantly improve the information transparency of the company. Thus, it improves managers' earnings manipulation behavior and indirectly affects ESG performance 9 . In summary, it is of great significance to analyze the direct and indirect impacts of DT on the ESG performance of enterprises and how to promote the ESG performance for digital technology to enable green development and promote the process of circular economy.…”
Section: Introductionmentioning
confidence: 99%